Self-stabilization precipitation polymerization method of Fischer-Tropsch synthesis product
By adding low-carbon olefins to Fischer Tropsch synthetic products for self-stable precipitation polymerization, the complexity of separation and utilization of α-olefins in Fischer Tropsch synthetic oil is solved, and the product separation and efficient utilization with simple process and low cost are achieved. Expand the application of functional copolymers.
Patent Information
- Application Number
- CN202411578891.9
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-11-06
- Publication Date
- 2025-01-10
- Estimated Expiration
- 2044-11-06
AI Technical Summary
The separation and utilization of α-olefins in the existing Fischer Tropsch synthetic oil has problems of complex process and high cost, especially the difficulty in product separation during the self-polymerization of long-chain α-olefins, and the utilization of α-olefins in Fischer Tropsch synthetic wax is insufficient. .
The self-stable precipitation polymerization method of adding low-carbon olefins as the third monomer to Fischer Tropsch synthetic product and electron accepting monomer is achieved through simple centrifugation to obtain alternating copolymer micro-polymers between electron donor and electron accepting monomer ball.
It has achieved the utilization of Fischer-Tropsch synthetic products with simple process, easy product separation, high production efficiency and low cost, overcomes the problem of high value utilization of long-chain α-olefins, and broadens the application scope of functional copolymers.
Smart Images

Figure CN119285852A_ABST
Abstract
Description
Technical Field
[0001] The invention belongs to the field of polymer synthesis, and in particular relates to a self-stabilizing precipitation polymerization method for a Fischer-Tropsch synthesis product. Background Art
[0002] Fischer-Tropsch Synthesis (FTS) is a chemical process developed by German scientists Franz Fischer and Hans Tropsch in 1925 to convert carbon- and hydrogen-rich gases (i.e., syngas) into liquid fuels and other chemical products. The original purpose of the technology was to explore a method for making liquid fuels from solid carbon resources (such as coal), especially in the face of the challenge of scarce oil resources. With the development of technology and the advancement of time, Fischer-Tropsch synthesis has evolved from a coal-dependent fuel production process to a technology with a wider range of applications. It can utilize a variety of carbon and hydrogen resources, including natural gas and biomass, to achieve the conversion from low-value carbon and hydrogen resources to high-value liquid fuels. At present, this technology is not only widely used in the production of liquid fuels, but also plays an important role in the production of chemical raw materials and products. It has great strategic significance for promoting energy diversification and fossil energy substitution.
[0003] The composition of Fischer-Tropsch synthetic oil is complex, mainly composed of alpha olefins, normal alkanes, oxygen-containing compounds and other substances, with carbon number distribution between C5 and C30. Among them, long-chain alpha olefins have high added value and account for about 60% of synthetic oil. Usually, Fischer-Tropsch synthetic oil needs to be hydrogenated and used as a blending oil component of gasoline. It has the characteristics of low sulfur, low aromatics and high cetane number, which can complement natural petroleum products. Heavy oil and heavy wax can be used as raw materials for hydrocracking, synthetic lubricants, etc. However, the above-mentioned treatment method is costly due to its complex process.
[0004] At present, the research on the value-added utilization of Fischer-Tropsch synthetic oil mainly includes separation and extraction of individual α-olefins. Individual α-olefins have industrial application value, such as 1-hexene and 1-octene can be used as polyethylene comonomers, and α-olefins with higher carbon numbers can be oxidized to prepare oxygen-containing compounds such as alcohols and sulfonates for use as detergents. There are also some reports on the polymerization of individual α-olefins with maleic anhydride. Through free radical polymerization, α-olefins can be converted into polymer resources.
[0005] Patent document 1 discloses a method and apparatus for separating 1-octene from Fischer-Tropsch oil-washed naphtha, wherein 1-octene is obtained by subjecting the oil-washed naphtha to distillation, deoxygenation, etherification and distillation.
[0006] Patent Document 2 and Patent Document 3 respectively disclose a method and apparatus for separating and purifying 1-decene and 1-dodecene from Fischer-Tropsch stable heavy oil, wherein the stable heavy oil is cut into narrow fractions and then subjected to a series of reactions to obtain 1-decene and 1-dodecene.
[0007] In non-patent documents 1 to 4, 1-hexene-maleic anhydride, 1-octene-maleic anhydride, 1-dodecene-maleic anhydride, 1-tetradecene-maleic anhydride, and 1-octadecene-maleic anhydride copolymers were prepared by using initiators such as dibenzoyl peroxide and azobisisobutyronitrile, selecting solvents such as toluene, xylene, acetone, and dioxane, and using precipitants such as methanol and n-hexane.
[0008] Patent document 4 proposes that Fischer-Tropsch synthetic oil can be copolymerized with electron-withdrawing functional monomers to directly obtain functional copolymers without separation, avoiding the problem of difficulty in self-polymerization by free radical polymerization due to the allyl radical effect of α-olefins, and achieving a higher yield.
[0009] References:
[0010] Patent Literature:
[0011] Patent document 1: CN 114805005 A;
[0012] Patent document 2: CN 114685235 A;
[0013] Patent document 3: CN 114644543 A;
[0014] Patent document 4: CN 117417481 A.
[0015] Non-patent literature:
[0016] Non-patent document 1: Nifant'ev IE et al., "Copolymers of Maleic Anhydride and Methylene Alkanes: Synthesis, Modification, and Pour Point Depressant Properties", Polymer Science, Series B, 2018, 60(4): 469-480;
[0017] Non-patent document 2: Demircan D et al., "Preparation of Poly(MA-alt-α-olefin-C6,8,12,18) / Silica Nanohybrids via in situ generated nanofillers for use as a dualfunction organonanofiller", Journal of Chemical Sciences, 2015, 127(11): 1993-2003;
[0018] Non-patent document 3: Davies MC et al., "Molar mass determination of poly(octadecene-alt-maleic anhydride)copolymers by size exclusion chromatography and dilute solution viscometry", Polymer, 2002, 43(15): 4311-4314;
[0019] Non-patent document 4: Chen Y et al., "A novel hyper-cross-linked polymer for high-efficient fluid-loss control in oil-based drilling fluid", Colloids and Surfaces A Physicochemical and Engineering Aspects, 2021, 626: 127004. Summary of the invention
[0020] Problem that the invention aims to solve
[0021] Patent Documents 1 to 3 relate to methods for separating α-olefins from Fischer-Tropsch synthetic oil products. Separating the individual α-olefins and then utilizing them will make the entire process complicated and costly.
[0022] In non-patent documents 1 to 4, α-olefin and maleic anhydride are copolymerized to obtain alternating copolymers of the two, and the anhydride groups are modified by esterification, amination and other reactions to obtain functionalized polymers containing long-chain alkyl groups, which show the great potential application value of such copolymers. However, the polymerization methods involved in non-patent documents 1 to 4 are all solution polymerizations, and the product separation is difficult, and a large amount of precipitant must be added to separate it.
[0023] In the method of Patent Document 4, due to the long alkyl chain of the long-chain α-olefin, the polymerization process can only be solution polymerization, and the product separation is difficult. Alkyl alcohol must be used as a precipitant to separate the product. On the one hand, alkyl alcohol will cause the ring-opening esterification reaction of maleic anhydride, and on the other hand, the separation method using a large amount of precipitant is not suitable for industrial production.
[0024] In addition, Fischer-Tropsch synthesis products also include Fischer-Tropsch synthesis wax, which contains less than 10% of α-olefins. The effective utilization of these olefins is also a problem that needs to be solved.
[0025] The technical problem to be solved by the present invention is to provide a method for effectively utilizing Fischer-Tropsch synthesis products with simple process, easy product separation, high production efficiency and low cost.
[0026] Solutions for solving problems
[0027] In view of the above problems, the inventors conducted long-term and in-depth research and found that the addition of low-carbon number olefins as the third monomer can achieve self-stabilizing precipitation polymerization of the Fischer-Tropsch synthesis product and the electron-accepting monomer. The system after polymerization can be separated from the solid by simple centrifugation to obtain alternating copolymer microspheres of the electron-donating monomer and the electron-accepting monomer, thereby completing the present invention.
[0028] Specifically, the present invention solves the problem of the present invention through the following solutions.
[0029] [1] A self-stabilizing precipitation polymerization method comprising the following steps:
[0030] A reaction system comprising a Fischer-Tropsch synthesis product, an electron accepting monomer, a low carbon number olefin, an initiator and a solvent is subjected to self-stabilizing precipitation polymerization;
[0031] The low carbon number olefin is ethylene and / or propylene;
[0032] The Fischer-Tropsch synthesis product comprises an electron donating monomer.
[0033] [2] The self-stabilizing precipitation polymerization method according to [1], wherein
[0034] The electron accepting monomer is one or a combination of two or more selected from maleic anhydride, maleimide, itaconic anhydride and their derivatives;
[0035] The Fischer-Tropsch synthesis product is Fischer-Tropsch synthesis oil and / or Fischer-Tropsch synthesis wax;
[0036] The initiator is one or more selected from azo compound initiators and peroxide initiators;
[0037] The solvent is an organic solvent.
[0038] [3] The self-stabilizing precipitation polymerization method according to [2], wherein
[0039] The Fischer-Tropsch synthetic oil is preferably Fischer-Tropsch synthetic oil washed naphtha and / or Fischer-Tropsch synthetic stable heavy oil; the mass content of the electron-donating monomer in the Fischer-Tropsch synthetic product is 1 to 70%; the electron-donating monomer is one or a combination of two or more selected from olefins having a carbon number of 4 to 40, preferably α-olefin;
[0040] The solvent is one or a combination of two or more selected from ketone solvents, carboxylic acid ester solvents and ether solvents;
[0041] The azo compound initiator is azobisisobutyronitrile or azobisisoheptanenitrile;
[0042] The peroxide initiator is dibenzoyl oxide, diisopropyl peroxide, di-tert-butyl peroxide, dodecyl peroxide, tert-butyl perbenzoate, diisopropyl peroxydicarbonate, and dicyclohexyl peroxydicarbonate.
[0043] [4] The self-stabilizing precipitation polymerization method according to any one of [1] to [3], wherein
[0044] In the reaction system, the total mass concentration of the electron-donating monomer and the electron-accepting monomer is 5% to 75%, preferably 10% to 60%;
[0045] Taking the total mass of the electron-donating monomer, the electron-accepting monomer and the low-carbon olefin as 100%, the mass fraction of the low-carbon olefin is 1 to 50%, preferably 3 to 40%, and more preferably 5 to 40%;
[0046] The mass ratio of the electron accepting monomer to the Fischer-Tropsch synthesis product is 1:30 to 5:1, preferably 1:8 to 5:4;
[0047] Based on the total mass of the electron accepting monomer, the electron donating monomer and the low carbon number olefin as 100%, the amount of the initiator is 0.05 to 10 wt%, preferably 1 to 5 wt%.
[0048] [5] A self-stabilizing precipitation polymerization method according to any one of [1] to [3], wherein the electron accepting monomer, initiator and Fischer-Tropsch synthesis product are mixed, and then the low carbon number olefin is added, so that the resulting reaction system undergoes self-stabilizing precipitation polymerization.
[0049] [6] A self-stabilizing precipitation polymerization method according to any one of [1] to [3], wherein the electron accepting monomer and the initiator are respectively added to the solvent and mixed, and then the Fischer-Tropsch synthesis product is added, and then an inert gas is introduced into the system, and then ethylene and / or propylene is introduced, and then the reaction system is heated to the polymerization reaction temperature to carry out self-stabilizing precipitation polymerization.
[0050] [7] The self-stabilizing precipitation polymerization method according to any one of [1] to [3], wherein the self-stabilizing precipitation polymerization is carried out in an inert gas, the polymerization reaction temperature is 50 to 120° C., and the polymerization reaction time is 1 to 24 hours.
[0051] [8] The self-stabilizing precipitation polymerization method according to any one of [1] to [3], further comprising a step of post-treating the reaction system after the self-stabilizing precipitation polymerization, wherein the post-treatment preferably comprises one or a combination of two or more of solid-liquid separation, washing or drying.
[0052] [9] A copolymer obtained by the self-stabilizing precipitation polymerization method according to any one of [1] to [8].
[0053]
[10] The copolymer according to [9], wherein the copolymer is copolymer microspheres having a number average particle size of 0.1 to 10 μm and a particle size distribution coefficient of 1.001 to 1.2.
[0054] Effects of the Invention
[0055] The self-stabilizing precipitation polymerization method for the Fischer-Tropsch synthesis product of the present invention has the characteristics of simple process, easy product separation, high production efficiency and low cost, and provides an effective solution to the problem of high-value utilization of long-chain α-olefins in Fischer-Tropsch synthesis products.
[0056] Specifically, the present invention has the following beneficial effects:
[0057] (1) The method of the present invention is simple in process and can realize self-stabilizing precipitation polymerization by simply adding low-carbon olefins. After polymerization, solid-liquid separation can be realized by simple treatment. The solvent in the supernatant obtained by separation can be recycled again, and the remainder is unreacted long-chain alkanes, which is suitable for industrial production.
[0058] (2) The method of the present invention can directly use unseparated Fischer-Tropsch synthesis products or fractions of Fischer-Tropsch synthesis products as raw materials without the need for refining and separation, thereby greatly reducing costs;
[0059] (3) The copolymer prepared by the method of the present invention has a high content of functional groups and can be functionalized by further modification, thereby broadening the application scope of the functional copolymer and making effective use of the resources of Fischer-Tropsch synthesis products.
[0060] (4) The method of the present invention overcomes the problem that the Fischer-Tropsch synthesis products are very complex in composition, have close boiling points, and are difficult to separate, which limits their application;
[0061] (5) In the method of the present invention, copolymers containing alkyl chains with different carbon numbers can be obtained by adjusting the monomer ratio or different types of Fischer-Tropsch products, so that the hydrophilicity and lipophilicity of the product copolymer can be easily controlled. BRIEF DESCRIPTION OF THE DRAWINGS
[0062] Figure 1 This is a SEM photo of the copolymer microspheres obtained in Example 1;
[0063] Figure 2 This is a SEM photo of the copolymer microspheres obtained in Example 2;
[0064] Figure 3 This is a SEM photo of the copolymer microspheres obtained in Example 7;
[0065] Figure 4 This is a SEM photo of the lower precipitate obtained in Comparative Example 2;
[0066] Figure 5 This is the SEM photograph of the lower precipitate obtained in Comparative Example 4. DETAILED DESCRIPTION
[0067] The following is a detailed description of the present invention. The technical features described below are described based on representative embodiments and specific examples of the present invention, but the present invention is not limited to these embodiments and specific examples.
[0068] <Terms and Definitions>
[0069] In this specification, "Fischer-Tropsch synthesis product" refers to the product obtained by the Fischer-Tropsch synthesis technology.
[0070] In this specification, "self-stabilizing precipitation polymerization" refers to a polymerization method in which no emulsifier is used in the polymerization system and the polymerization product is suspended in the reaction medium.
[0071] In this specification, "particle size" refers to the number average particle size of the particles being described, which can be obtained by the method described in the Examples section.
[0072] In this specification, "electron accepting monomer" refers to a monomer having an electron withdrawing group on the carbon-carbon double bond participating in the polymerization reaction.
[0073] In this specification, "electron donating monomer" refers to a monomer having an electron donating group on the carbon-carbon double bond that participates in the polymerization reaction.
[0074] In the present specification, unless otherwise specifically stated, "alkyl group" means a linear, branched or cyclic alkyl group.
[0075] In this specification, the numerical range expressed using "a numerical value A to a numerical value B" means a range including the endpoints numerical values A and B.
[0076] In the present specification, a numerical range expressed using "above" or "below" means a numerical range including the number.
[0077] In this specification, the word "may" means both performing a certain process and not performing a certain process.
[0078] In this specification, the use of "optionally" or "optional" indicates that certain substances, components, execution steps, application conditions and other factors are used or not used.
[0079] In this specification, the unit names used are all international standard unit names, and unless otherwise stated, the "%" used indicates weight or mass percentage.
[0080] In this specification, the references to "preferred embodiments", "embodiments", etc., mean that the specific elements (e.g., features, structures, properties and / or characteristics) described in connection with the embodiments are included in at least one embodiment described herein, and may or may not exist in other embodiments. In addition, it should be understood that the elements may be combined in various embodiments in any suitable manner.
[0081] <Self-stabilizing precipitation polymerization method>
[0082] An object of the present invention is to provide a self-stabilizing precipitation polymerization method, characterized in that it comprises the following steps:
[0083] A reaction system comprising a Fischer-Tropsch synthesis product, an electron accepting monomer, a low carbon number olefin, an initiator and a solvent is subjected to self-stabilizing precipitation polymerization;
[0084] The carbon number of the low carbon number olefin is 2 to 4;
[0085] The Fischer-Tropsch synthesis product comprises an electron donating monomer.
[0086] In previous studies, the copolymerization of Fischer-Tropsch synthesis products and electron-accepting monomers can only be carried out through solution polymerization. This solution polymerization method has the problem of difficulty in product separation, and alkyl alcohol must be used as a precipitant to separate the product. Since α-olefins have long-chain alkyl groups, the cohesive energy density of the copolymer is too low. The inventors have tried to change the solvent solubility parameters, monomer concentration and increase the molecular weight, but they were unable to achieve self-stabilizing precipitation polymerization of Fischer-Tropsch synthesis products and electron-accepting monomers. However, in a study, the inventors unexpectedly discovered that the use of low-carbon olefins as the third monomer for copolymerization can achieve self-stabilizing precipitation polymerization of Fischer-Tropsch synthesis products, thereby completing the present invention.
[0087] In the method of the present invention, the competitive polymerization rates of low-carbon olefins and α-olefins are similar, and the two participate in polymerization simultaneously to obtain an alternating copolymer of electron-donating monomers and electron-accepting monomers. The solubility parameter of the polymer is increased by adding low-carbon olefins as the third monomer, thereby realizing self-stabilizing precipitation polymerization of Fischer-Tropsch synthesis products and α-olefins.
[0088] The method of the invention has the characteristics of simplicity, low cost, etc., and provides a new approach to solving the problem of high-value utilization of 60% long-chain alpha-olefins in Fischer-Tropsch synthetic oil.
[0089] Various aspects of the self-stabilizing precipitation polymerization process of the present invention are described in detail below.
[0090] Reaction system
[0091] The reaction system of the self-stabilizing precipitation polymerization method of the present invention comprises a Fischer-Tropsch synthesis product, an electron accepting monomer, a low carbon number olefin, an initiator and a solvent.
[0092] Fischer-Tropsch synthesis products are the products of Fischer-Tropsch synthesis technology. Their components include normal alkanes, normal olefins, branched alkanes, branched olefins and normal alcohols, among which normal alkanes and normal olefins are the main components, and the olefin components are mostly α-olefins.
[0093] The present invention has no particular restrictions on the composition of the Fischer-Tropsch synthesis product, as long as it includes an electron-donating monomer that can copolymerize with the electron-accepting monomer, and those skilled in the art can make specific selections according to needs. The Fischer-Tropsch synthesis product can be an unseparated Fischer-Tropsch synthesis oil product, or different fractions of the Fischer-Tropsch synthesis oil product, or a Fischer-Tropsch synthesis wax, as long as it contains an electron-donating monomer.
[0094] Preferably, the mass content of the electron donating monomer in the Fischer-Tropsch synthesis product is 1-70%, preferably 5-65%, more preferably 20-65%, for example 30%, 40%, 50%, 60%, etc.
[0095] Preferably, the electron-donating monomer is one or a combination of two or more selected from olefins having 4 to 40 carbon atoms, preferably α-olefins, more preferably 1-butene, 1-pentene, 1-hexene, 1-heptene, 1-octene, 1-nonene, 1-decene, 1-undecene, 1-dodecene, 1-tridecene, 1-tetradecene, 1-pentadecene, 1-hexadecene, 1-heptadecene, 1-octadecene, 1-nonadecene, 1-eicosene, 1-undecene, 1-undecene, 1-dodecene, 1-tridecene, 1-tetradecene, 1-pentadecene, 1-hexadecene, 1-tricosene, 1-tetradecene, 1-pentacosene, 1-hexacosene, 1-heptacosene, 1-octacosene, 1-nonacosene, 1-triacos ...
[0096] In one embodiment, the Fischer-Tropsch synthesis product is a Fischer-Tropsch synthesis oil and / or a Fischer-Tropsch synthesis wax, wherein the Fischer-Tropsch synthesis oil is preferably a Fischer-Tropsch synthesis oil washed naphtha and / or a Fischer-Tropsch synthesis stable heavy oil. The Fischer-Tropsch synthesis oil washed naphtha mainly contains components from C4 to C14, wherein about 60 to 70% of α-olefins are contained. The Fischer-Tropsch synthesis stable heavy oil mainly contains components from C8 to C30, wherein about 55 to 65% of α-olefins are contained. The Fischer-Tropsch synthesis heavy wax mainly contains components with higher carbon numbers (above C30), wherein about 1 to 10% of α-olefins are contained.
[0097] The inventors have found that components other than α-olefins in the Fischer-Tropsch synthesis product, such as normal alkanes, branched alkanes and other components, can be used as the medium of the reaction system. These media can also be separated after the polymerization is completed and continue to be used as products such as gasoline and diesel.
[0098] In the present invention, an electron accepting monomer is used to polymerize with an electron donating monomer in a Fischer-Tropsch synthesis product, thereby obtaining a functional copolymer having a functional group. Further, the functional group may be an anhydride group, an imide group, or the like.
[0099] In one embodiment, the electron accepting monomer is one or a combination of two or more selected from maleic anhydride, maleimide, itaconic anhydride and derivatives thereof.
[0100] Preferably, the electron accepting monomer is one or a combination of two or more selected from maleic anhydride, itaconic anhydride, maleimide, N-phenylmaleimide, N-methylmaleimide, N-ethylmaleimide, and N-(1-naphthyl)maleimide.
[0101] In one embodiment, in the reaction system, the total mass concentration of the electron-donating monomer and the electron-accepting monomer is 5% to 75%, preferably 10% to 60%, for example, 15%, 20%, 25%, 30%, 35%, 40%, 45%, 50%, 55%, 65%, etc. By making the total mass concentration of the electron-donating monomer and the electron-accepting monomer within the above range, the polymerization reaction can be better performed.
[0102] In one embodiment, the mass ratio of the electron accepting monomer to the Fischer-Tropsch synthesis product is 1:30 to 5:1, preferably 1:8 to 5:4, for example: 1:25, 1:20, 1:15, 1:10, 1:5, 1:3, 1:2, 1:1, 2:1, 3:1, 4:1, etc.
[0103] In one embodiment, based on the total mass of electron-donating monomers, electron-accepting monomers and low-carbon olefins as 100%, the mass fraction of low-carbon olefins is 1 to 50%, preferably 3 to 40%, more preferably 5 to 40%, for example 8%, 10%, 15%, 20%, 22%, 23%, 25%, 27%, 30%, etc.
[0104] In the present invention, an initiator is used to polymerize the electron accepting monomer with the electron donating monomer in the Fischer-Tropsch synthesis product. In one embodiment, the initiator is one or more selected from an azo compound initiator and a peroxide initiator. Preferably, the peroxide initiator is dibenzoyl oxide, diisopropyl peroxide, di-tert-butyl peroxide, dodecyl peroxide, tert-butyl perbenzoate, diisopropyl peroxydicarbonate, dicyclohexyl peroxydicarbonate, etc.; the azo compound initiator is azobisisobutyronitrile, azobisisoheptylonitrile, etc.
[0105] In one embodiment, based on the total mass of the electron accepting monomer, the electron donating monomer in the Fischer-Tropsch synthesis product and the low carbon number olefin as 100%, the content of the initiator is 0.05-10wt%, preferably 0.5-5wt%, more preferably 1-5wt%; for example: 0.1wt%, 0.5wt%, 1wt%, 2.5wt%, 3.5wt%, 4wt%, 4.5wt%, 7wt%, 9wt%, etc. When the content of the initiator is 0.05-10wt%, the desired functional copolymer can be obtained.
[0106] The present invention does not specifically limit the solvent, and it can be a commonly used solvent in the art. Specifically, the solvent is an organic solvent, and preferably, the organic solvent includes one or a combination of two or more of a ketone solvent, a carboxylic acid ester solvent, and an ether solvent.
[0107] The carboxylate solvent may have a structure as shown in the following formula (I):
[0108]
[0109] In formula (2), R4 is a hydrogen atom, a C1-C6 alkyl group or a C6-C10 aryl group, and R5 is a C1-C8 alkyl group or a C6-C10 aryl group; specifically, the C6-C10 aryl group can be a phenyl group, a benzyl group, a phenethyl group, or the like.
[0110] Specific examples of the carboxylic acid ester solvent may be ethyl formate, propyl formate, isobutyl formate, pentyl formate, ethyl acetate, butyl acetate, isobutyl acetate, pentyl acetate, isoamyl acetate, benzyl acetate, phenyl acetate, methyl propionate, ethyl propionate, propyl propionate, butyl propionate, methyl butyrate, ethyl butyrate, propyl butyrate, butyl butyrate, isobutyl butyrate, isoamyl butyrate, ethyl isobutyrate, ethyl isovalerate, isoamyl isovalerate, methyl benzoate, ethyl benzoate, propyl benzoate, butyl benzoate, isoamyl benzoate, methyl phenylacetate, ethyl phenylacetate, propyl phenylacetate, butyl phenylacetate, isoamyl phenylacetate, and the like, or an ester solvent of a combination of two or more thereof.
[0111] The ketone solvent can be selected from one or a combination of two or more of acetone, butanone, cyclohexanone, methyl isobutyl ketone, methyl isopropyl ketone and the like.
[0112] The ether solvent can be selected from one or a combination of two or more of dimethyl ether, methyl ethyl ether, ethyl ether, ethyl propyl ether, dipropyl ether, dibutyl ether, methyl propyl ether, methyl butyl ether, methyl isobutyl ether, methyl tert-butyl ether, methyl isopentyl ether, methyl tert-amyl ether, methyl cyclopentyl ether, ethylene glycol dimethyl ether, ethylene glycol diethyl ether, tetrahydrofuran, tetrahydropyran, 1,4-dioxane, etc.
[0113] The present invention does not impose any particular limitation on the amount of solvent used, and the solvent can be added as needed, as long as the electron accepting monomer, Fischer-Tropsch synthesis product, low-carbon olefin and initiator can be fully dissolved and the polymerization product is insoluble in the solvent.
[0114] Preferably, the mass ratio of the solvent to the electron acceptor monomer is (10-1):1, preferably (8-2):1, for example (7-3):1 or (6-4):1.
[0115] Preferably, the solubility parameter of the copolymer as the polymerization product is 1 to 7 MPa greater than the solubility parameter of the organic solvent by selecting the solvent. 1 / 2 , preferably 2~5MPa 1 / 2 .
[0116] The solubility parameter of a polymer has the usual meaning in the art and can be calculated using the indirect method, i.e., using the contribution of each group in the molecular structure, by the following formula:
[0117] δ=ρ∑F i / M
[0118] Where, δ is the solubility parameter of the polymer; F i is the molar gravitational constant of each group component in the polymer molecule; ρ is the density of the polymer; M is the chain molecular weight of the polymer.
[0119] For the solubility parameters of solvents, those skilled in the art can look them up in technical manuals or public literature in the field, for example, the solubility parameters of various solvents are recorded in "Polymer Physics" (Hua Youqing, Jin Riguang, Chemical Industry Press, 2013, page 83).
[0120] Polymerization process
[0121] In the present invention, there is no particular limitation on the order and method of mixing the components in the reaction system, and the components can be mixed in any appropriate manner and order.
[0122] In a specific embodiment, the self-stabilizing precipitation polymerization method of the present invention comprises the following steps: mixing the electron accepting monomer, initiator, and Fischer-Tropsch synthesis product and adding the low carbon number olefin, so that the obtained reaction system undergoes self-stabilizing precipitation polymerization.
[0123] In a specific embodiment, the self-stabilizing precipitation polymerization method of the present invention comprises the following steps: after mixing the electron accepting monomer with the initiator, adding the Fischer-Tropsch synthesis product, and then adding the low carbon number olefin, so that the resulting reaction system undergoes self-stabilizing precipitation polymerization.
[0124] The solvent may be added to the reaction system at any appropriate time. Preferably, the electron accepting monomer and the initiator are added to the solvent separately and mixed.
[0125] The polymerization reaction is started by heating the reaction system to the polymerization reaction temperature. For the polymerization reaction temperature, it can be 50-120°C, preferably 60-110°C, for example: 55°C, 60°C, 65°C, 70°C, 75°C, 80°C, 85°C, 90°C, 95°C, 100°C, 105°C, 110°C, 115°C, etc. For the polymerization reaction time, it can be 1-24 hours, for example: 2 hours, 5 hours, 8 hours, 10 hours, 12 hours, 15 hours, 18 hours, 20 hours, 22 hours, etc. Further, the polymerization reaction is carried out under the protection of an inert gas, specifically, the inert gas can be nitrogen or argon.
[0126] In a more specific embodiment, the electron accepting monomer and the initiator are respectively added to a solvent and mixed, and then the Fischer-Tropsch synthesis product is added, and then an inert gas is introduced into the reaction system, followed by ethylene and / or propylene, and then the reaction system is heated to the polymerization reaction temperature to carry out self-stabilizing precipitation polymerization.
[0127] Based on the characteristics of the self-stabilizing precipitation polymerization method itself, the reaction medium has a good dissolving effect on the electron-accepting monomer and the initiator, and is miscible with the low-carbon number olefin monomer to ensure a homogeneous system before the reaction. However, the reaction medium cannot dissolve the generated copolymer. When the polymer molecular chain reaches a certain critical length, it precipitates from the reaction medium. However, the precipitated polymer cannot precipitate in the form of powder or block as in precipitation polymerization, but is stably suspended in the reaction medium in the form of microspheres or particles, forming a stable dispersion system similar to a polymer emulsion.
[0128] In a specific embodiment, the self-stabilizing precipitation polymerization method of the present invention further comprises a step of post-treating the reaction system after the self-stabilizing precipitation polymerization, wherein the post-treatment preferably comprises one or a combination of two or more of solid-liquid separation, washing or drying.
[0129] Based on the characteristics of the self-stabilizing precipitation polymerization method itself, the reaction system obtained after the polymerization is a dispersed system of copolymer microspheres. Therefore, there is no need to use a precipitant, and the copolymer microspheres can be separated only by solid-liquid separation.
[0130] More specifically, after the polymerization reaction, the reaction system is subjected to solid-liquid separation, and the separated solid (copolymer microspheres) is optionally dried.
[0131] Solid-liquid separation can be performed by known methods, such as filtration, centrifugation, evaporation of the solvent, and the like.
[0132] The washing can be performed by eluting the separated solid with a washing solvent, dispersing the separated solid in a washing solvent and then performing solid-liquid separation again, etc. The washing solvent is preferably the solvent used in the reaction.
[0133] Drying can be performed by methods known in the art, such as heating to evaporate the residual solution. The drying temperature can be 40 to 150° C., such as 40 to 100° C., and the drying time can be 1 to 48 hours, such as 4 to 40 hours or 8 to 30 hours.
[0134] <Copolymer>
[0135] The present invention also relates to a copolymer obtained by the method of the present invention. The copolymer of the present invention is a copolymer of olefin and electron accepting monomer, wherein the olefin includes low carbon number olefin and olefin from Fischer-Tropsch synthesis product.
[0136] The copolymer of the present invention is a copolymer microsphere, and its number average particle size is 0.1-10 μm, preferably 0.2-8 μm, more preferably 0.3-5 μm, and further preferably 0.4-3 μm; for example, 0.5 μm, 0.6 μm, 0.7 μm, 0.8 μm, 0.9 μm, 1.2 μm, 1.4 μm, 1.5 μm, 1.6 μm, 0.5 μm, 1.9 μm, 2.2 μm, 2.4 μm, 2.6 μm, 2.8 μm, 2.9 μm, etc.
[0137] The particle size distribution coefficient is 1.001 to 1.2, preferably 1.003 to 1.15, more preferably 1.005 to 1.1, for example 1.006 to 1.06.
[0138] In the copolymer microspheres obtained by the method of the present invention, the content of residual solvent is 5 mass % or less, preferably 3 mass % or less, more preferably 2 mass % or less, and even 1 mass % or less.
[0139] In one embodiment, the polymer may have a number average molecular weight of 1,000 to 500,000, preferably 2,000 to 200,000, and further preferably 2,500 to 100,000, such as 50,000, 20,000, 10,000, 8,000, and the like, as measured by gel permeation chromatography.
[0140] Example
[0141] The embodiments of the present invention will be described in detail below in conjunction with the examples, but it will be appreciated by those skilled in the art that the following examples are only used to illustrate the present invention and should not be considered as limiting the scope of the present invention. If no specific conditions are specified in the examples, the conditions are carried out according to normal conditions or the conditions recommended by the manufacturer. If the manufacturer is not specified for the reagents or instruments used, they are all conventional products that can be obtained commercially.
[0142] The composition of the Fischer-Tropsch synthetic oil-washed naphtha (also referred to as "oil-washed naphtha") used in the following examples is shown in Table 1 below:
[0143] Table 1
[0144]
[0145] The composition of the Fischer-Tropsch synthesis stable heavy oil (also referred to as "stable heavy oil") used in the following examples is shown in Table 2 below:
[0146] Table 2
[0147]
[0148] The composition of the Fischer-Tropsch wax used in the following examples (average carbon number is 22.13) is shown in Table 3 below:
[0149] Table 3
[0150] type content α-Olefins 10.53% Internal Olefins 13.19% Normal alkanes 76.28%
[0151] Example 1
[0152] 18 g of maleic anhydride and 1.65 g of dibenzoyl peroxide (BPO) were dissolved in 90 g of methyl tert-butyl ether solvent, dissolved and mixed uniformly by ultrasound to obtain a transparent solution, and then 20 g of Fischer-Tropsch synthetic oil-washed naphtha was added. Nitrogen was passed through the system for 10 minutes, and then 3 g of propylene gas was introduced. The system was reacted at a constant temperature of 80°C for 6 hours to obtain a dispersed system of maleic anhydride and α-olefin copolymer microspheres. The system was then centrifuged and vacuum dried at 80°C for 24 hours to obtain white solid maleic anhydride and α-olefin copolymer microspheres.
[0153] Example 2
[0154] 18 g of maleic anhydride and 1.65 g of dibenzoyl peroxide were dissolved in 90 g of methyl tert-butyl ether solvent, dissolved and mixed uniformly by ultrasound to obtain a transparent solution, and then 10 g of Fischer-Tropsch synthetic oil-washed naphtha was added. Nitrogen was passed through the system for 10 minutes, and then 9 g of propylene gas was introduced. The system was reacted at a constant temperature of 80°C for 6 hours to obtain a dispersed system of maleic anhydride and α-olefin copolymer microspheres. The system was then centrifuged and vacuum dried at 80°C for 24 hours to obtain white solid maleic anhydride and α-olefin copolymer microspheres.
[0155] Example 3
[0156] 18 g of maleic anhydride and 1.65 g of dibenzoyl peroxide were dissolved in 90 g of isoamyl acetate solvent, dissolved and mixed uniformly by ultrasound to obtain a transparent solution, and then 20 g of Fischer-Tropsch synthetic oil-washed naphtha was added. Nitrogen was passed through the system for 10 minutes, and then 3 g of propylene gas was introduced. The system was reacted at a constant temperature of 80°C for 6 hours to obtain a dispersed system of maleic anhydride and α-olefin copolymer microspheres. The system was then centrifuged and vacuum dried at 80°C for 24 hours to obtain white solid maleic anhydride and α-olefin copolymer microspheres.
[0157] Example 4
[0158] 18 g of maleic anhydride and 1.65 g of dibenzoyl peroxide were dissolved in a mixed solvent of 27 g of ethyl acetate and 63 g of cyclohexane, and dissolved and mixed uniformly by ultrasound to obtain a transparent solution. Then, 20 g of Fischer-Tropsch synthetic oil-washed naphtha was added, and nitrogen was passed through the system for 10 minutes. Then, 3 g of propylene gas was introduced and the system was reacted at a constant temperature of 80°C for 6 hours to obtain a dispersed system of maleic anhydride and α-olefin copolymer microspheres. The system was then centrifuged and vacuum dried at 80°C for 24 hours to obtain white solid maleic anhydride and α-olefin copolymer microspheres.
[0159] Example 5
[0160] 18 g of maleic anhydride and 1.65 g of dibenzoyl peroxide were dissolved in a mixed solvent of 27 g of butanone and 63 g of cyclohexane, and dissolved and mixed uniformly by ultrasound to obtain a transparent solution. Then, 20 g of Fischer-Tropsch synthetic oil-washed naphtha was added, and nitrogen was passed through the system for 10 minutes. Then, 3 g of propylene gas was introduced and the system was reacted at a constant temperature of 80°C for 6 hours to obtain a dispersed system of maleic anhydride and α-olefin copolymer microspheres. The system was then centrifuged and vacuum dried at 80°C for 24 hours to obtain white solid maleic anhydride and α-olefin copolymer microspheres.
[0161] Example 6
[0162] 18 g of maleic anhydride and 1.65 g of azobisisobutyronitrile (AIBN) were dissolved in 90 g of methyl tert-butyl ether solvent, dissolved and mixed uniformly by ultrasound to obtain a transparent solution, and then 20 g of Fischer-Tropsch synthetic oil-washed naphtha was added. Nitrogen was passed through the system for 10 minutes, and then 3 g of propylene gas was introduced. The system was reacted at a constant temperature of 70°C for 6 hours to obtain a dispersed system of maleic anhydride and α-olefin copolymer microspheres. The system was then centrifuged and vacuum dried at 70°C for 24 hours to obtain white solid maleic anhydride and α-olefin copolymer microspheres.
[0163] Example 7
[0164] 18 g of maleic anhydride and 1.65 g of dibenzoyl peroxide were dissolved in 90 g of methyl tert-butyl ether solvent, dissolved and mixed uniformly by ultrasound to obtain a transparent solution, and then 15 g of Fischer-Tropsch synthesis stable heavy oil was added. Nitrogen was passed through the system for 10 minutes, and then 6 g of propylene gas was introduced. The system was reacted at a constant temperature of 80°C for 6 hours to obtain a dispersed system of maleic anhydride and α-olefin copolymer microspheres. The system was then centrifuged and vacuum dried at 80°C for 24 hours to obtain white solid maleic anhydride and α-olefin copolymer microspheres.
[0165] Example 8
[0166] 18 g of maleic anhydride and 1.65 g of dibenzoyl peroxide were dissolved in 90 g of isoamyl acetate solvent, dissolved and mixed uniformly by ultrasound to obtain a transparent solution, and then 15 g of Fischer-Tropsch synthesis stable heavy oil was added. Nitrogen was passed through the system for 10 minutes, and then 6 g of propylene gas was introduced. The system was reacted at a constant temperature of 80°C for 6 hours to obtain a dispersed system of maleic anhydride and α-olefin copolymer microspheres. The system was then centrifuged and vacuum dried at 80°C for 24 hours to obtain white solid maleic anhydride and α-olefin copolymer microspheres.
[0167] Example 9
[0168] 18 g of itaconic anhydride and 1.65 g of dibenzoyl peroxide were dissolved in 90 g of methyl tert-butyl ether solvent, dissolved and mixed uniformly by ultrasound to obtain a transparent solution, and then 20 g of Fischer-Tropsch synthetic oil-washed naphtha was added. Nitrogen was passed through the system for 10 minutes, and then 3 g of propylene gas was introduced. The system was kept at a constant temperature of 80°C for 6 hours to obtain a dispersed system of maleic anhydride and α-olefin copolymer microspheres. The system was then centrifuged and vacuum dried at 80°C for 24 hours to obtain itaconic anhydride and α-olefin copolymer microspheres as white solids.
[0169] Example 10
[0170] 18 g of maleimide and 1.65 g of dibenzoyl peroxide were dissolved in 90 g of methyl tert-butyl ether solvent, dissolved and mixed uniformly by ultrasound to obtain a transparent solution, and then 20 g of Fischer-Tropsch synthetic oil-washed naphtha was added. Nitrogen was passed through the system for 10 minutes, and then 3 g of propylene gas was introduced. The system was reacted at a constant temperature of 80°C for 6 hours to obtain a dispersed system of maleic anhydride and α-olefin copolymer microspheres. The system was then centrifuged and vacuum dried at 80°C for 24 hours to obtain white solid maleimide and α-olefin copolymer microspheres.
[0171] Embodiment 11
[0172] 18 g of maleic anhydride and 1.65 g of dibenzoyl peroxide were dissolved in 90 g of methyl tert-butyl ether solvent, dissolved and mixed uniformly by ultrasound to obtain a transparent solution, and then 20 g of Fischer-Tropsch synthetic oil-washed naphtha was added. Nitrogen was passed through the system for 10 minutes, and then 3 g of ethylene gas was introduced. The system was reacted at a constant temperature of 80°C for 6 hours to obtain a dispersed system of maleic anhydride and α-olefin copolymer microspheres. The system was then centrifuged and vacuum dried at 80°C for 24 hours to obtain white solid maleic anhydride and α-olefin copolymer microspheres.
[0173] Example 12
[0174] 18 g of maleic anhydride and 1.65 g of dibenzoyl peroxide were dissolved in 90 g of methyl tert-butyl ether solvent, dissolved and mixed uniformly by ultrasound to obtain a transparent solution, and then 15 g of Fischer-Tropsch synthesis stable heavy oil was added. Nitrogen was passed through the system for 10 minutes, and then 6 g of ethylene gas was introduced. The system was reacted at a constant temperature of 80°C for 6 hours to obtain a dispersed system of maleic anhydride and α-olefin copolymer microspheres. The system was then centrifuged and vacuum dried at 80°C for 24 hours to obtain white solid maleic anhydride and α-olefin copolymer microspheres.
[0175] Example 13
[0176] 18 g of maleic anhydride and 1.65 g of dibenzoyl peroxide were dissolved in 90 g of methyl tert-butyl ether solvent, dissolved and mixed uniformly by ultrasound to obtain a transparent solution, and then 15 g of Fischer-Tropsch wax (purchased from Ningmei Group) was added. Nitrogen was passed through the system for 10 minutes, and then 6 g of propylene gas was passed through the system. The system was reacted at a constant temperature of 80°C for 6 hours to obtain a dispersed system of maleic anhydride and α-olefin copolymer microspheres. The system was then centrifuged and vacuum dried at 80°C for 24 hours to obtain white solid maleic anhydride and α-olefin copolymer microspheres.
[0177] Comparative Example 1
[0178] 0.49g of maleic anhydride and 0.024g of azobisisobutyronitrile were dissolved in 0.50g of cyclohexanone solvent, ultrasonically dissolved and mixed to obtain a transparent solution, then 1.01g of Fischer-Tropsch oil-washed naphtha was added, nitrogen was passed through the system for 10 minutes, and the reaction was carried out at a constant temperature of 70°C for 6 hours to obtain a transparent reaction solution; the reaction solution was added to anhydrous ethanol for precipitation to obtain a precipitated product; the precipitated product was centrifuged at a speed of 7000 rpm for 5 minutes, and ethanol was added for washing and centrifugation three times. Finally, vacuum drying was performed to constant weight to obtain 0.59g of Fischer-Tropsch oil-washed naphtha-maleic anhydride copolymer with a yield of 53%.
[0179] Comparative Example 2
[0180] 18g of maleic anhydride and 1.65g of dibenzoyl peroxide were dissolved in 90g of methyl tert-butyl ether solvent, ultrasonically dissolved and mixed to obtain a transparent solution, and then 25g of Fischer-Tropsch oil-washed naphtha was added. The system was vented with nitrogen for 10 minutes, and the reaction was carried out at a constant temperature of 80°C for 6h to obtain a layered system of a hard precipitate layer and a supernatant. The hard precipitate was taken out and dried to constant weight to obtain 20.5g of Fischer-Tropsch oil-washed naphtha-maleic anhydride copolymer, and the yield of the precipitate was 62%. The supernatant was then added to anhydrous ethanol for precipitation to obtain a small amount of supernatant precipitate; the supernatant precipitate was centrifuged at a speed of 7000 rpm for 5 minutes, and ethanol was added for washing and centrifugation three times, and vacuum dried to constant weight to obtain 1.98g of Fischer-Tropsch oil-washed naphtha-maleic anhydride copolymer, with a yield of 6% in the supernatant and a total yield of 68%.
[0181] Comparative Example 3
[0182] 0.72g maleic anhydride and 0.088g azobisisobutyronitrile were dissolved in 2.4716g isoamyl acetate solvent, ultrasonically dissolved and mixed to obtain a transparent solution, then 1.81g Fischer-Tropsch synthesis stable heavy oil was added, nitrogen was passed through the system for 10 minutes, and the reaction was carried out at 70°C for 8 hours to obtain a transparent reaction solution; the reaction solution was added to anhydrous ethanol for precipitation to obtain a precipitated product; the precipitated product was centrifuged at a speed of 7000 rpm for 5 minutes, and ethanol was added for washing and centrifugation three times. Finally, vacuum drying was performed to constant weight to obtain 1.21g of Fischer-Tropsch synthesis stable heavy oil-maleic anhydride copolymer with a yield of 69%.
[0183] Comparative Example 4
[0184] 18g of maleic anhydride and 1.65g of dibenzoyl peroxide were dissolved in 90g of methyl tert-butyl ether solvent, ultrasonically dissolved and mixed to obtain a transparent solution, and then 25g of Fischer-Tropsch synthesis stable heavy oil was added. The system was vented with nitrogen for 10 minutes, and the reaction was carried out at a constant temperature of 80°C for 6 hours to obtain a layered system of a hard precipitate layer and a supernatant. A small amount of hard precipitate was taken out and dried to constant weight to obtain 2.97g of Fischer-Tropsch synthesis stable heavy oil-maleic anhydride copolymer, and the yield of the precipitate was 9%. The supernatant was then added to anhydrous ethanol for precipitation to obtain a large amount of supernatant precipitate; the supernatant precipitate was centrifuged at a speed of 7000 rpm for 5 minutes, and ethanol was added for washing and centrifugation three times, and vacuum dried to constant weight to obtain 27.4g of Fischer-Tropsch synthesis stable heavy oil-maleic anhydride copolymer, with a yield of 83% in the supernatant and a total yield of 91%.
[0185] <Testing and Evaluation>
[0186] SEM analysis
[0187] A small amount of the dried copolymer microspheres obtained in Examples 1, 2 and 7 and the lower precipitate obtained in Comparative Examples 2 and 4 were dispersed in an appropriate amount of polymerization solvent, and after being uniformly dispersed by ultrasonication, the dispersion was dropped onto a cover glass, dried naturally, and the morphology was observed by a field emission scanning electron microscope (produced by JEOL, model: JSM7401). SEM photos of the copolymer microspheres of Examples 1, 2 and 7 were obtained, as shown in FIG. Figures 1 to 3 As shown; Comparative Examples 2 and 4 lower sediment SEM photos as shown Figure 4 and Figure 5 shown.
[0188] Particle size analysis
[0189] The particle size and distribution data of the copolymer microspheres obtained in Examples 1 to 13 were obtained by the following method:
[0190] First, the particle size and particle size distribution of the microspheres in the scanning electron microscope photograph are measured using measurement statistics software, and the particle size and distribution of the measured microspheres can be calculated using formulas 1 to 3.
[0191]
[0192] U=D w / D n Formula (3)
[0193] in:
[0194] D n ——Number average particle size of polymer microspheres;
[0195] D w ——Weight average particle size of polymer microspheres:
[0196] D i ——the particle size of the i-th microsphere;
[0197] N——total number of microspheres;
[0198] U——Dispersion coefficient of microsphere particle size.
[0199] Molecular weight test
[0200] Using tetrahydrofuran as eluent, the copolymer sample solutions obtained in Examples 1 to 13 and Comparative Examples 1 to 4 were accurately prepared with a concentration of 5 mg / mL, and the molecular weight of the copolymers was tested by gel permeation chromatography.
[0201] The various properties and evaluation results of the copolymer microspheres obtained in Examples 1 to 11 and Comparative Examples 1 to 4 are shown in Table 4.
[0202] Table 4
[0203]
[0204] As shown in Table 4, by adding ethylene or propylene as a low carbon number olefin, different types of Fischer-Tropsch synthesis products can achieve self-stable precipitation polymerization in different solvents, and microspheres with particle sizes ranging from 1 to 2.5 μm are obtained, and the product yield is above 50%. The method of the present invention can achieve self-stable precipitation polymerization of Fischer-Tropsch synthesis oil or Fischer-Tropsch synthesis wax.
[0205] Industrial Applicability
[0206] The method of the invention can be widely used in industry to prepare functional copolymer microspheres.
Claims
1. A self-stabilizing precipitation polymerization method, characterized in that: The following steps are involved: A reaction system comprising a Fischer-Tropsch synthesis product, an electron accepting monomer, a low carbon number olefin, an initiator and a solvent is subjected to self-stabilizing precipitation polymerization; The low carbon number olefin is ethylene and / or propylene; The Fischer-Tropsch synthesis product comprises an electron donating monomer.
2. The self-stabilizing precipitation polymerization method according to claim 1, characterized in that The electron accepting monomer is one or a combination of two or more selected from maleic anhydride, maleimide, itaconic anhydride and their derivatives; The Fischer-Tropsch synthesis product is Fischer-Tropsch synthesis oil and / or Fischer-Tropsch synthesis wax; The initiator is one or more selected from azo compound initiators and peroxide initiators; The solvent is an organic solvent.
3. The self-stabilizing precipitation polymerization method according to claim 2, characterized in that The Fischer-Tropsch synthetic oil is preferably Fischer-Tropsch synthetic oil washed naphtha and / or Fischer-Tropsch synthetic stable heavy oil; the mass content of the electron-donating monomer in the Fischer-Tropsch synthetic product is 1 to 70%; the electron-donating monomer is one or a combination of two or more selected from olefins having a carbon number of 4 to 40, preferably α-olefin; The solvent is one or a combination of two or more selected from ketone solvents, carboxylic acid ester solvents and ether solvents; The azo compound initiator is azobisisobutyronitrile or azobisisoheptanenitrile; The peroxide initiator is dibenzoyl oxide, diisopropyl peroxide, di-tert-butyl peroxide, dodecyl peroxide, tert-butyl perbenzoate, diisopropyl peroxydicarbonate, and dicyclohexyl peroxydicarbonate.
4. The self-stabilizing precipitation polymerization method according to any one of claims 1 to 3, characterized in that In the reaction system, the total mass concentration of the electron-donating monomer and the electron-accepting monomer is 5% to 75%, preferably 10% to 60%; Taking the total mass of the electron-donating monomer, the electron-accepting monomer and the low-carbon olefin as 100%, the mass fraction of the low-carbon olefin is 1 to 50%, preferably 3 to 40%, and more preferably 5 to 40%; The mass ratio of the electron accepting monomer to the Fischer-Tropsch synthesis product is 1:30 to 5:1, preferably 1:8 to 5:4; Based on the total mass of the electron accepting monomer, the electron donating monomer and the low carbon number olefin as 100%, the amount of the initiator is 0.05 to 10 wt%, preferably 1 to 5 wt%.
5. The self-stabilizing precipitation polymerization method according to any one of claims 1 to 3, characterized in that After the electron accepting monomer, initiator and Fischer-Tropsch synthesis product are mixed, the low carbon number olefin is added, so that the obtained reaction system undergoes self-stabilizing precipitation polymerization.
6. The self-stabilizing precipitation polymerization method according to any one of claims 1 to 3, characterized in that The electron accepting monomer and the initiator are respectively added to the solvent and mixed, and then the Fischer-Tropsch synthesis product is added, and then an inert gas is introduced into the system, and then ethylene and / or propylene is introduced, and then the reaction system is heated to the polymerization reaction temperature to carry out self-stabilizing precipitation polymerization.
7. The self-stabilizing precipitation polymerization method according to any one of claims 1 to 3, characterized in that The self-stabilizing precipitation polymerization is carried out in an inert gas, the polymerization reaction temperature is 50 to 120° C., and the polymerization reaction time is 1 to 24 hours.
8. The self-stabilizing precipitation polymerization method according to any one of claims 1 to 3, characterized in that The method further comprises a step of post-treating the reaction system after the self-stabilizing precipitation polymerization, wherein the post-treatment preferably comprises one or a combination of two or more of solid-liquid separation, washing or drying.
9. A copolymer obtained by the self-stabilizing precipitation polymerization process according to any one of claims 1 to 8.
10. The copolymer according to claim 9, characterized in that The copolymer is copolymer microspheres, the number average particle size is 0.1-10 μm, and the particle size distribution coefficient is 1.001-1.2.
Citation Information
Patent Citations
Method and device for separating and purifying 1-dodecene from Fischer-Tropsch synthesis stable heavy oil
CN114644543A
Method and device for separating 1-decene from Fischer-Tropsch synthesis stable heavy oil
CN114685235A
Method and device for separating 1-octene from Fischer-Tropsch synthesis oil washing naphtha
CN114805005A
Self-stabilization precipitation polymerization method using ether-containing solvent
CN115926024A
Functional copolymer and preparation method thereof
CN117417481A
Cited By
Aldehyde group-containing polymer and preparation method thereof
CN119859209A
Self-stabilization precipitation polymerization method of Fischer-Tropsch synthesis product
CN120484169A
Precipitation polymerization method of Fischer-Tropsch synthesis product and functionalized cross-linked copolymer microspheres prepared by precipitation polymerization method
CN121319263A